SMEs navigating COVID-19: The influence of social capital and dynamic capabilities on organizational resilience - Ozanne, Lucie K.; Chowdhury, Mesbahuddin; Prayag, Girish; Mollenkopf, Diane A. (Industrial marketing management, 2022)
Building the resilience capacity of businesses is important for economic, social and community recovery during the COVID-19 pandemic, yet organizational resilience is under-examined in the marketing literature. Crises and disasters can significantly impact small and medium enterprises (SMEs), affecting their ability to mitigate, respond and recover. Social capital (SC) is a key resource that can be mobilized by SMEs to tap the resources embedded in internal and external relationships to respond to disruptions, yet the mechanism through which SC facilitates organizational resilience is not clear. Using middle-range theorizing, we propose dynamic capabilities (DC) as the key sensing, seizing and reconfiguration resources that transform SC into organizational resilience. The results from a sample of SMEs (n = 419) in Australia and New Zealand demonstrate that internal SC has a positive effect on external SC (customer-focused). Only internal SC has a direct effect on organizational resilience. DC partially and fully mediates the relationship between internal and external SC and organizational resilience respectively. Implications for theory and practice are offered. •Examines the impact of COVID-19 on SMEs downunder and the key role that customer plays in response and recovery.•Confirms internal SC positively impacts external SC (customer-focused).•Internal SC has a positive effect on organizational resilience.•DC partially mediates the relationship between internal social capital and organizational resilience.•DC fully mediates the relationship between external social capital and organizational resilience.